Switching-based cooperative decode-and-forward relaying for hybrid FSO/RF networks - Sharma, Shubha (2020)
In this paper, we propose a switching scheme for a hybrid free-space optical (FSO)/radio frequency (RF) system with a selective decode-and-forward (DF) relay network. Specifically, the system transmits over FSO channels when the instantaneous signal-to-noise ratio (SNR) at the FSO receiver is greater than the threshold SNR. If the SNR drops below the threshold, the system switches and transmits over RF channels. The exact outage probability and average symbol error rate (SER) expressions are derived for a selective DF relay network with maximal ratio combining (MRC) assumed at the destination. In addition, the asymptotic outage and SER expressions with a lower computational complexity are derived and the diversity order is determined. The optimum value of the threshold SNR, which satisfies the target SER, has been calculated numerically for the proposed switching scheme. The theoretical results, which are validated by Monte Carlo simulations, show that the proposed switching scheme for a cooperative hybrid FSO/RF system drastically improves the performance compared to that of a single-hop (SH) switching-based hybrid FSO/RF and cooperative FSO systems.